Effects of Ru(ii/iii) redox on the Co(ii) coordination number and magnetic properties of 1D cyanide-bridged Co–Ru compounds. Issue 4 (22nd December 2016) - Zhu, Xiaoquan; Su, Shaodong; Cao, Wenhai; Hu, Shengmin; Wen, Yuehong; Wu, Xintao; Sheng, Tianlu
Abstract : Two new Co–Ru one-dimensional cyanide-bridged compounds with different Ru valences and Co coordination types display different magnetic properties. Abstract : A new 1D cyanide-bridged Co–Ru compound, {[ trans -Ru III (dmap)4 (CN)2 Co(dipic)(MeOH)](PF6 )} n (1a ) (dmap = 4-dimethylaminopyridine, dipic = pyridine-2, 6-dicarboxylate), and its reduced state, [ trans -Ru II (dmap)4 (CN)2 Co(dipic)] n (1b ) have been synthesized. Upon the Ru center reduction fromiii toii, the MeOH solvent molecule bound to Co(ii ) in1a is expelled.1a displays ferrimagnetic properties but1b is only a paramagnetic compound.